Review of ’Preparing for Surgery: A Pocket Guide with Insights from an Anesthesia Provider to Help Prepare for Surgery with Confidence’ and its Implications in Public Health - Acharya, Krishna Prasad; Shrestha, Ava (A Bi-annual South Asian Journal of Research & Innovation, 2023)
"Preparing for Surgery: A Pocket Guide with Insights from an Anesthesia Provider to Help Prepare for Surgery with Confidence" by Dana Adams (2024) is a concise and accessible resource designed to guide readers through the complexities of surgical preparation. The book demystifies the surgical process, addressing common anxieties and questions related to anesthesia and pre- and post-operative care. It emphasizes patient education and advocacy, empowering readers to actively participate in their surgical journey. Beyond its direct relevance to surgery, the book carries implications for public health by promoting patient education and understanding of surgical procedures. This can contribute to reduced anxiety, improved compliance with pre- and post-operative instructions, and better surgical outcomes. The book also fosters stronger patient-provider relationships, increasing trust and satisfaction with healthcare services. With its clear explanations and practical advice, this book serves as an informative companion for patients, students, and practitioners alike, ultimately contributing to a more informed and positive surgical experience.